1999
DOI: 10.1016/s0009-9236(99)70105-0
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of pefloxacin and enoxacin with the human cytochrome P450 enzyme CYP1A2

Abstract: Enoxacin and to a lesser extent pefloxacin may cause clinically relevant interactions with further CYP1A2 substrates. The data suggest that the pefloxacin interaction is partly mediated by its major metabolite norfloxacin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 40 publications
1
11
0
3
Order By: Relevance
“…This was in contrast to the findings at steady state (d 5) that the co-administration of ATFX on d 1 did not alter the plasma concentrations of TP or the urinary excretion of TP metabolites ( Figure 1 and Table 1), although the ATFX concentrations in plasma on d 1 were higher than those on d 5 Table 2). Similar phenomena were found for the effects of tosufloxacin on TP plasma concentrations and the effects of enoxacin on caffeine concentrations [20,27] . The in vitro results using human liver microsomes showed that ATFX is a weak reversible inhibitor of CYP1A2, but ATFX appears to be a clinically relevant inhibitor.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This was in contrast to the findings at steady state (d 5) that the co-administration of ATFX on d 1 did not alter the plasma concentrations of TP or the urinary excretion of TP metabolites ( Figure 1 and Table 1), although the ATFX concentrations in plasma on d 1 were higher than those on d 5 Table 2). Similar phenomena were found for the effects of tosufloxacin on TP plasma concentrations and the effects of enoxacin on caffeine concentrations [20,27] . The in vitro results using human liver microsomes showed that ATFX is a weak reversible inhibitor of CYP1A2, but ATFX appears to be a clinically relevant inhibitor.…”
Section: Discussionsupporting
confidence: 78%
“…The non-renal clearance (Cl nr ) was designed to be Cl/F-Cl r . Analysis of the differences between the pharmacokinetic parameters of drug alone and the combination of drugs was handled as an equivalence problem [20] . Comparison of pharmacokinetic parameters was carried out with analysis of variance (ANOVA)-based 90% confidence intervals (CI) after log-transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Since they all induce CYP1A2 enzymes in humans, the mechanism for the increased caffeine metabolism is increased amounts of CYP1A1 and CYP1A2 in the liver. In agreement with this notion, other CYP1A enzyme inducing xenobiotics, like omeprazol, cause a similar type of effect (Nousbaum et al, 1994;Kinizig-Schippes et al, 1999). Secondly, a prolonged half-life of caffeine is observed when the catalysis via CYP1A2 is reduced, either due to inhibition by the si-multaneous presence of specific CYP1A2 xenobiotic inhibitors or due to reduced amount of the enzyme being present in the liver (Kalow, 1985).…”
Section: Metabolism In the Adult Human Beingmentioning
confidence: 85%
“…A number of the quinolones have been found to reduce the hepatic metabolism of coadministered drugs such as the xanthines theophylline and caffeine [171][172][173][174][175][176][177][178][179][180] (Table 9.2). In contrast to the absorption interactions with multivalent cations, which appear to be generalizable to the entire quinolone drug class, differences do exist between individual quinolones in their propensity to inhibit hepatic xanthine metabolism.…”
Section: Metabolism Interactionsmentioning
confidence: 99%